Crystal structure of (2-amino-7-methyl-4-oxidopteridine-6-carboxylato-κ3O4,N5,O6)aqua(1,10-phenanthroline-κ2N,N′)copper(II) trihydrate - Siddhartha S. Baisya; Parag S. Roy (Acta Crystallographica Section E, 2014)
In the title compound, [Cu(C8H5N5O3)(C12H8N2)(H2O)]·3H2O, the CuII cation is O,N,O′-chelated by the 2-amino-7-methyl-4-oxidopteridine-6-carboxylate anion and N,N′-chelated by the 1,10-phenanthroline (phen) ligand. A water molecule further coordinates to the CuII cation to complete the elongated distorted octahedral coordination geometry. In the molecule, the pteridine ring system is essentially planar [maximum deviation = 0.055 (4) Å], and its mean plane is nearly perpendicular to the phen ring system [dihedral angle = 85.97 (3)°]. In the crystal, N—H...O, O—H...N and O—H...·O hydrogen bonds, as well as weak C—H...O hydrogen bonds and C—H...π interactions, link the complex molecules and lattice water molecules into a three-dimensional supramolecular architecture. Extensive π–π stacking between nearly parallel aromatic rings of adjacent molecules are also observed, the centroid-to-centroid distances being 3.352 (2), 3.546 (3), 3.706 (3) and 3.744 (3) Å.